2013
DOI: 10.3349/ymj.2013.54.5.1119
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Anticoagulation during Off Pump Coronary Artery Bypass in Patients Recently Exposed to Clopidogrel

Abstract: PurposeThe aim of this study was to find an optimal range of activated clotting time (ACT) during off-pump coronary artery bypass surgery (OPCAB) yielding ischemic protection without the risk of hemorrhagic complications in patients with recent exposure to dual antiplatelet therapy.Materials and MethodsThree hundred and five patients who received aspirin and clopidogrel within 7 days of isolated multi-vessel OPCAB were retrospectively studied. Combined hemorrhagic and ischemic outcome was defined as the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 36 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…Some of them included only patients with a high pretest probability (eg, enlarged, positron emission tomography-positive lymph nodes) or excluded patients with lymph nodes that would not likely be accessed by EBUS. 2,3 The sensitivity in our study, which included patients with normal-sized lymph nodes and inaccessible lymph nodes by EBUS, and excluded patients with bulky lymph nodes, is lower than that in the previous reports. Especially in patients with normal mediastinum on computed tomography and positron emission tomography, we encountered difficulty detecting mediastinal metastases by EBUS-TBNA.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…Some of them included only patients with a high pretest probability (eg, enlarged, positron emission tomography-positive lymph nodes) or excluded patients with lymph nodes that would not likely be accessed by EBUS. 2,3 The sensitivity in our study, which included patients with normal-sized lymph nodes and inaccessible lymph nodes by EBUS, and excluded patients with bulky lymph nodes, is lower than that in the previous reports. Especially in patients with normal mediastinum on computed tomography and positron emission tomography, we encountered difficulty detecting mediastinal metastases by EBUS-TBNA.…”
mentioning
confidence: 65%
“…We thank Smith 1 and Saha 2 for their comments in response to our article regarding graft patency in the Danish On-pump Versus Off-pump Randomization Study. 3 They have noted that a high proportion of the graft obstructions were found at the proximal anastomoses, which they believe should not be influenced by the use of cardiopulmonary bypass.…”
Section: Definition Of Proximal Anastomosis In the Doors Study Reply mentioning
confidence: 99%
See 2 more Smart Citations
“…used activated clotting time (ACT) as a measure of systemic heparinization instead of standardizing the dose of heparin. [ 12 ] Tanaka et al . studied the effects of varying doses of heparin used for systemic heparinization in patients undergoing OPCAB and concluded that total dose of heparin and protamine required in OPCAB was lower than that of surgery conducted under CPB.…”
Section: Introductionmentioning
confidence: 99%